2017
DOI: 10.1089/neu.2016.4615
|View full text |Cite
|
Sign up to set email alerts
|

Selective Brain Hypothermia Mitigates Brain Damage and Improves Neurological Outcome after Post-Traumatic Decompressive Craniectomy in Mice

Abstract: Hypothermia and decompressive craniectomy (DC) have been considered as treatment for traumatic brain injury. The present study investigates whether selective brain hypothermia added to craniectomy could improve neurological outcome after brain trauma. Male CD-1 mice were assigned into the following groups: sham; DC; closed head injury (CHI); CHI followed by craniectomy (CHI+DC); and CHI+DC followed by focal hypothermia (CHI+DC+H). At 24 h post-trauma, animals were subjected to Neurological Severity Score (NSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 133 publications
2
23
0
Order By: Relevance
“…Similar to our previous studies and other reports, TBI produces behavioral abnormalities and neurodegenerative changes resulting from regional patterns of cell death and circuit dysfunction [21,44]. As supported by previous studies of TTM on TBI, we also demonstrated that using CCI rats as an in vivo model that TTM attenuated several phenotypes of animal post-TBI, markedly reduced cell death [7,8,11], BBB leakage [45][46][47], cortical lesion volume [48], cerebrovascular histopathology [49,50], and improved behavioral and pathological outcomes [51]. These results may help determine both the safety and efficacy for postinjury TTM, and such laboratory models (in vitro or in vivo) may present an ideal opportunity for the application of proteomic technological approach to biomarker discovery after TBI.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our previous studies and other reports, TBI produces behavioral abnormalities and neurodegenerative changes resulting from regional patterns of cell death and circuit dysfunction [21,44]. As supported by previous studies of TTM on TBI, we also demonstrated that using CCI rats as an in vivo model that TTM attenuated several phenotypes of animal post-TBI, markedly reduced cell death [7,8,11], BBB leakage [45][46][47], cortical lesion volume [48], cerebrovascular histopathology [49,50], and improved behavioral and pathological outcomes [51]. These results may help determine both the safety and efficacy for postinjury TTM, and such laboratory models (in vitro or in vivo) may present an ideal opportunity for the application of proteomic technological approach to biomarker discovery after TBI.…”
Section: Discussionsupporting
confidence: 91%
“…To achieve reported neuroprotective effects of hypothermia without risk of previously mentioned systemic side effects, selective, or focal brain cooling got into focus. Some previous studies (conducted also by our group, see Figure 1 ) were able to report a limitation of brain edema formation due to focal application of hypothermia ( 20 , 39 45 ).…”
Section: Introductionmentioning
confidence: 66%
“…There are previously multiple papers that suggested targeted brain cooling as a reasonable treatment option to patient with severe traumatic brain injury [21][22][23][24][25][26][27][28][29][30][31][32][33]. Targeted brain cooling is a good alternative to systemic hypothermia, as systemic hypothermia has serious side effects such as circulatory constrain, increased risk of infection, electrolyte imbalance, and coagulopathy [15][16][17][18].…”
Section: Current Evidences On the Usage Of Direct Brain Cooling In Trmentioning
confidence: 99%
“…Jacek et al [33] suggested in their animal study that selective brain hypothermia, which is applied via a cranial window after decompressive craniectomy seems to be reducing posttraumatic structural and functional damage. However, the study is actually limited by small rodent model and also short observational period.…”
Section: Current Evidences On the Usage Of Direct Brain Cooling In Trmentioning
confidence: 99%